REPREZENTACIJA ŽENSKE – UMETNICE V SODOBNEM SLOVENSKEM ROMANU: (Dekleva: Pimlico, Bojetu: Ptičja hiša) (Filološke studije, 2019)
The characters in contemporary Slovene novel are often established in descriptive and mimetical dimensions of its gender. The establishment of identity develops within broader social context – usually in a patriarchal social structure. The usage of different narrators, changes in focalization and different perspectives, such as irony, parody, grotesque, show the instability and fluidity of a contemporary subject, as well as the dynamics of gender construction. The traditional and sometimes stereotypical role of a woman is being exceeded by these narrative strategies. The main female characters in Dekleva’s novel Pimlico and Bojetu’s Ptičja hiša differ from the traditionally passive heroine by trying to establish their identity in the field of art. Art is in Pimlico considered as the only possibility for expressing the human – female essence of being. In Ptičja hiša both heroines try to escape the social repression through art. The female principle is being transformed into an active one, heading into the future or into the more human world. Nevertheless, the female action can not change the position of a human being in a modern society. The woman, as well as the man, is alienated and alone in a modern world, although she changes her gender-related role.